2005
DOI: 10.1093/ajcn.82.1.76
|View full text |Cite
|
Sign up to set email alerts
|

Co-ingestion of a protein hydrolysate and amino acid mixture with carbohydrate improves plasma glucose disposal in patients with type 2 diabetes

Abstract: The combined ingestion of carbohydrate with a protein hydrolysate and amino acid mixture significantly increases de novo insulin production in patients with a long-term diagnosis of type 2 diabetes. The increased insulin response stimulates plasma glucose disposal and reduces postprandial glucose concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
88
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(96 citation statements)
references
References 34 publications
5
88
3
Order By: Relevance
“…As such, leucine co-ingestion has been suggested as an effective strategy to further augment the insulinotropic effects of protein co-ingestion. In accordance, we established that co-ingestion of a protein hydrolysate/ leucine mixture with carbohydrate can be used to augment endogenous insulin secretion, accelerate blood glucose disposal and to attenuate the postprandial rise in glucose concentrations in type 2 diabetes patients (van Loon et al, 2003;Manders et al, 2005Manders et al, , 2006a. More recently, we showed that co-ingestion of such a protein/amino-acid mixture with every main meal can be used as an effective nutritional intervention strategy to reduce the prevalence of daily postprandial hyperglycemia by B26% in these patients (Manders et al, 2006b).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…As such, leucine co-ingestion has been suggested as an effective strategy to further augment the insulinotropic effects of protein co-ingestion. In accordance, we established that co-ingestion of a protein hydrolysate/ leucine mixture with carbohydrate can be used to augment endogenous insulin secretion, accelerate blood glucose disposal and to attenuate the postprandial rise in glucose concentrations in type 2 diabetes patients (van Loon et al, 2003;Manders et al, 2005Manders et al, , 2006a. More recently, we showed that co-ingestion of such a protein/amino-acid mixture with every main meal can be used as an effective nutritional intervention strategy to reduce the prevalence of daily postprandial hyperglycemia by B26% in these patients (Manders et al, 2006b).…”
Section: Discussionmentioning
confidence: 82%
“…Such a defect is indicative of a progressive insensitivity of the b-cell to glucose (Porte and Kahn, 2001). Even though insulin secretion in response to glucose ingestion is blunted in long-standing type 2 diabetes patients, we have shown that co-ingestion of a protein hydrolysate/leucine mixture can stimulate endogenous insulin secretion resulting in a 2-4-fold greater postprandial insulin response (van Loon et al, 2003;Manders et al, 2005Manders et al, , 2006a. This increased postprandial insulin response has been shown to accelerate glucose disposal, attenuating the postprandial rise in blood glucose concentrations in these type 2 diabetes patients .…”
Section: Introductionmentioning
confidence: 76%
“…In particular, milk proteinderived peptides have beneficial effects on the cardiovascular, gastrointestinal, immune and nervous systems (9) . Whey proteins (WP) and caseins (CN) may aid in minimising the physiological effects of T2DM and have been shown to stimulate insulin secretion and regulate blood glucose in T2DM subjects (10,11) . Recent research has also shown that peptides derived from milk proteins have DPP-IV inhibitory properties (12,13) .…”
Section: Proceedings Of the Nutrition Societymentioning
confidence: 99%
“…Previous research has demonstrated that co-ingestion of proteins with carbohydrates results in increased plasma insulin responses (Rabinowitz et al, 1966;Pallotta and Kennedy, 1968), both in healthy subjects (van Loon et al, 2000;Calbet and MacLean, 2002) and in patients with type II diabetes (Nuttall et al, 1984;Manders et al, 2005Manders et al, , 2006. The effect of proteins on insulin secretion is mainly a consequence of the effect that specific amino acids in the blood have on pancreatic b-cell activity (Newsholme et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of proteins on the carbohydrateinduced insulin response has been studied most frequently, since this is of interest in type II diabetic patients (van Loon et al, 2000;Manders et al, 2005Manders et al, , 2006. Although glucagon is not an as extensively studied hormone as insulin, glucagon secretion is disturbed in both type I and type II diabetic patients.…”
Section: Introductionmentioning
confidence: 99%